PENGARUH BELANJA PEMERINTAH DAERAH TERHADAP KINERJA PENYELENGGARAAN PEMERINTAH DAERAH - Marihot Nasution (Pusat Kajian Anggaran, 2019)
This study examines how local government spending affects public services provided to the public. The performance of public service delivery is measured by the achievement of the performance of local government operations which are the object of evaluation in the Evaluasi Kinerja Penyelenggaraan Pemerintahan Daerah (EKPPD) which is carried out annually by the Ministry of Home Affairs. Whereas government expenditure is regional government expenditure per function per capita. Using a sample of 94 local governments, this study took the period 2014 to 2018. The results showed that per capita expenditure function had a positive effect on the performance of local government administration for regional government authority in education, health and infrastructure (housing and public facilities). The capital expenditure ratio is also tested to see the effect of capital expenditure on the performance of public service delivery. In testing the performance of the health and infrastructure sectors, this ratio has a significant negative effect, but for the performance of the education sector this ratio has no significant effect. This means that capital expenditures incurred by local governments have not been effective in meeting the needs of public services for the community, especially in the field of education.